Workshop on internship coordination management for year 2018, Faculty of Hotel and Tourism Management / Aida Khalida Mohamed Idris and Wan Hayati Wan Bujang - Mohamed Idris, Aida Khalida; Wan Bujang, Wan Hayati (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Four lecturers who were in charge of the students’ internship program at Hotel and Tourism Management Centre of Studies, Penang were invited by the Dean to FPHP Puncak Alam campus for a two-day workshop. The workshop was held on the 24th - 25th of September, 2018 at the Banquet Hall, Hotel UiTM Puncak Alam. The workshop was also attended by other internship coordinators from the Faculty of Hotel and Tourism Management of other UiTM campuses such as Terengganu, Melaka, Sabah and Sarawak campuses. On the first day, the delegates were introduced to the new Head of Internship coordinator, Pn. Alina Shuhaida Mohammad Ramly from Puncak Alam Campus.In the opening speech delivered by the Deputy Dean of Academic Affairs, FPHP, Associate Professor Dr. Norzuwana Sumarjan, it was emphasized that the main reason for the workshop was to ensure that there would be some improvement made so that any changes done would be consistent at each campus, thus ensuring a more effective internship management by the campuses.